2021
DOI: 10.1007/s11332-021-00745-8
|View full text |Cite|
|
Sign up to set email alerts
|

COVID-19 nationwide lockdown and physical activity profiles among North-western Italian population using the International Physical Activity Questionnaire (IPAQ)

Abstract: Background The role of physical activity in enhancing health is well recognized. However, in the more industrialized countries, physical activity rates are declining, and the emerging COVID-19 pandemic may amplify this scenario. Thus, this study aimed to report the Italian population’s physical activity profile living in the North-western regions during the national lockdown. Methods Physical activity was assessed using the official Italian short form of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Besides, since there is an important correlation between sedentary behavior and low mood, the issue of reducing sedentary time during the period of social isolation may be stressed for beneficial effects during lockdown but also for future wellbeing [16]. People should be encouraged to maintain a moderate amount of physical activity during the quarantine, particularly women, who are usually less active than men [17]. Since COVID-19 women were less physically active than men and reported more barriers and fewer facilitators to physical activity, they experienced significantly more generalized anxiety than men and showed significantly lower mental health scores [18].…”
Section: Reduced Physical Activity During Lockdownmentioning
confidence: 99%
“…Besides, since there is an important correlation between sedentary behavior and low mood, the issue of reducing sedentary time during the period of social isolation may be stressed for beneficial effects during lockdown but also for future wellbeing [16]. People should be encouraged to maintain a moderate amount of physical activity during the quarantine, particularly women, who are usually less active than men [17]. Since COVID-19 women were less physically active than men and reported more barriers and fewer facilitators to physical activity, they experienced significantly more generalized anxiety than men and showed significantly lower mental health scores [18].…”
Section: Reduced Physical Activity During Lockdownmentioning
confidence: 99%
“…Even though pupils were instructed by coaches to practise home-based physical activities, it can be argued that either general and unguided exercise assignments of 45–50 min 2 days per week were insufficient to retain adolescent physical fitness or that assignments’ compliance was not respected, if not both. It has been demonstrated that more experienced athletes of the same regional area (4 years of experience or more) who have had the opportunity to be remotely assisted, guided, and monitored by their coaches were more engaged in home training than their recreational counterparts, being able to keep high physical activity levels even in an extraordinary situation such as a nationwide lockdown [ 44 ]. It can be suggested that during training restriction periods, recreational athletes may need more thorough fitness programs with more detailed instructions and stricter surveillance than high-level athletes in order for home-based training to be effective.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, more attention to the physical appearance has been paid by the young generations, particularly in the industrialized regions and then in Northern Italy. In a recent interview performed among North−western Italian population, aimed to investigate the PA profile during the COVID-19 lockdown, 61.8% of interweaved people were moderately active, being tendentially young people more active than adults or elderly ( 45 ). On the contrary, data reported by the Italian Institute of Statistics show inactivity levels of nearly 50% among populations of southern Italy, with only about 20% of older adults practicing continuous PA ( 46 ).…”
Section: Discussionmentioning
confidence: 99%